Attenuation of testosterone-induced benign prostatic hyperplasia with Andrographis paniculata (burm.f.) leaf extract in Wistar rats - Etti, Imaobong Christopher; Unoh, Erimimoh Eba; Akpan, Mary Richard; Umanah, Ubong Uduak; Agbonika, Rebecca Emmanuel; Kadir, Arifah Abdul; Nwafor, Chukwuemeka (Taylor and Francis, 2024)
Andrographis paniculata (Burm.f.) Nees has been used traditionally in treating many diseases. This study investigated its potential to attenuate benign prostatic hyperplasia (BPH) in male rats. Rats were castrated, divided into five groups and orally treated for 14 days with: normal saline,10 mg/kg testosterone propionate sc, finasteride (0.5 mg/kg), 500 mg, and 1500 mg/kg of Andrographis paniculata. Relative prostate weights, the correlation between prostatic index and volume and the prostates’ histopathology as well as Prostate Specific Antigen (PSA) were evaluated. Following treatment with Andrographis paniculata, the prostate weights were significantly reduced (p < 0.05) and the lost correlation observed in the untreated group was restored. Histopathological assessment showed reduced epithelial hyperplasia following treatment with a resultant thin layer of epithelial cells, similar to the healthy normal control group. The level of PSA was also reduced. Andrographis paniculata, thus, has the potential to inhibit the proliferation observed in testosterone-induced BPH.